AKTIVITAS ANTIBAKTERI OBAT KUMUR HYDROGEL KARAGENAN TERHADAP Phorphyromonas gingivalis - atttallah, maisie; Bakar, Abu; Citra, Lestari (Universitas Baiturrahmah, 2025)
Introduction: Porphyromonas gingivalis is a Gram-negative anaerobic bacterium involved in the pathogenesis of periodontal disease that can destroy tooth tissue and cause tooth loss. Carrageenan is one of the natural ingredients that can be utilized as a medicinal and antibacterial plant. Aim: The purpose of this study was to determine the antibacterial activity of carrageenan gel mouthwash against Porphyromonas gingivalis bacteria. Methods: Carrageenan extract was prepared and formulated into a mouthwash gel. The antibacterial activity of carrageenan gel mouthwash against Porphyromonas gingivalis was evaluated at concentrations of 0.5%, 1%, 2%, and 4%, as well as a positive control using chlorhexidine and a negative control using distilled water. This test was conducted using the disc paper diffusion method. Result: The 4% carrageenan gel mouthwash demonstrated a statistically significant antibacterial effect against Porphyromonas gingivalis (mean inhibition zone: 2.125 mm; p = 0.001). Lower concentrations (0.5 %, 1 %, and 2 %) showed no inhibitory activity. While the effect of the 4 % formulation was categorized as weak compared to chlorhexidine control, the results confirm its potential as an antimicrobial agent. Conclusion: The 4% carrageenan gel mouthwash demonstrated significant antibacterial activity against Porphyromonas gingivalis (p=0.001), indicating its potential as a bioactive agent in oral care. Further studies are needed to evaluate its clinical efficacy and safety. Keywords: antibacterial, carrageenan, mouthwash, periodontitis